Application of Religious Tolerance Character Through Civics Learning at Madrasah Ibtidaiyah - Hermansyah, Yus; Hasanudin, Hasanudin; Nurishlah, Laesti; Nursholihah, Siti (Jurnal Ilmiah Wahana Pendidikan, 2022)
The application of religious tolerance character in PKN learning in Madrasah Ibtidaiyah has several effective approaches. One of them is by including material about religions in Indonesia in the PKN curriculum. The purpose of this study is to analyze the application of religious tolerance character through PKN learning in Madrasah Ibtidaiyah. The research method used is library research. The results showed that the use of diverse and interactive learning methods is an effective strategy in promoting religious tolerance among Madrasah Ibtidaiyah students. Open discussions allow students to share views and understanding, while case studies and visits to places of worship can provide immersive, hands-on experience. The importance of the role of teachers in shaping attitudes of religious tolerance has been proven in the literature. The teacher is not only a teacher, but also a model for students in terms of attitudes and behavior. In addition, a school culture that supports respect for differences also contributes greatly to creating an inclusive and tolerant environment